Blood count, endocrine, immunologic, renal, and hepatic markers in a case-control animal study of induced periodontitis in female rodents - Estarreja, João; Pimenta, Ana Clara; Botelho, João; Vilares, Arminda Maria; Mendes, José João; Rocha, João; Pinto, Rui; Mateus, Vanessa; Machado, Vanessa (Frontiers in Physiology, 2024)
Introduction: Periodontitis is a non-communicable chronic inflammatory disease with a systemic burden. Animal models of induced periodontitis help elucidate the mechanisms by which periodontal inflammation drives systemic effects. Studying this systemic involvement over longer follow-up periods may provide a strong foundation for future research on the association between diseases and periodontitis, particularly in female rats. Therefore, we aimed to compare blood, endocrine, immunologic, renal, and hepatic markers in a rat model of induced periodontitis in females with their control counterparts. Methods: Experimental periodontitis was induced in 20 female Wistar rats by the application and maintenance of silk ligatures on the upper molars. The rats were then assessed for macroscopical analysis, complete blood count, and biochemical, endocrine, and immunologic markers at 21, 28, 42, and 56 days. Results: Chronic periodontal inflammation was observed after 42 days of exposure to the ligatures. Additionally, it was also possible to notice significant systemic manifestations, such as the reduction of triiodothyronine and thyroxine levels, along with an increase in the expression of alkaline phosphatase, gamma-glutamyl transpeptidase, and lactate dehydrogenase. Discussion: The study’s findings imply that certain changes can be underscored to highlight a reduced risk of conception. Notably, previous investigations have indicated that subfertile women exhibit lower levels of thyroid hormones and elevated lactate dehydrogenase expression. Despite the absence of preclinical data delineating a possible association between periodontitis and female infertility, the results of this study may prove to be a crucial contribution to both the scientific and medical fields.